The impact of 1992 on European integration and relations with the United States - Wilhelm Nölling (Intereconomics, 1988)
The end of 1992 has of late become quite a significant date in Europe. By this time the so-called Single European Market is to be created. The date and the topic are producing intensive debates all over the world. The purpose of this article is to describe certain trends which go along with the process of approaching 1992 and which could have significant implications for the development of the world economy. What intentions do the Europeans have? Where do the risks and conflicts lie? What should be done in order to achieve a harmonious development in the relations between the USA and Europe?
Keywords: 330; Single European Market